Inferential trends towards error, scientific literacy and critical thinking: Pedagogical implications - Torres Bravo, Leyla (Opción, 2015)
In this paper I review the thesis set out by Thagard (2011) and some of the ideas taken on again in Thagard and Nussbaum (2014) about the existence of bias or tendencies towards error in human inferential activities, which lead us to make mistakes and move us away from scientific knowledge. I will analyze their main proposals and, specifically, their implications on decision making and on scientific literacy through critical thinking. In particular, I will focus on the revision of motivated inference and inference driven by fear through which the intent is to demonstrate the need for guiding us towards overcoming beliefs so, in this way, we make correct decisions about what we must believe and do in day-to-day and academic environments.